2018
DOI: 10.1536/ihj.17-206
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Blood Pressure Variations in Postmenopausal Females with Hypertension

Abstract: The abnormalities of blood pressure (BP) nocturnal decline have been found to be predictive for carotid plaque and lacunar infarction in patients with hypertension. In this study, BP dipping patterns in postmenopausal females with hypertension were investigated. The nocturnal decline of systolic BP (SBP) was evaluated using 24-hour ambulatory BP monitoring (ABPM). A total of 163 postmenopausal females were eventually included in our study. The prevalence of reverse-dipper BP pattern was 32.3% in females with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Increases in SBP, cSBP, central and peripheral MAP, and cPP were observed in the hypertensive elderly females of our study compared to males, and these findings are in accordance with those of previous reports [29][30][31]. We used an oscillometric technique to measure brachial blood pressure, and a noninvasive tonometric system was used to analyze the pulse wave of the radial artery.…”
Section: Discussionsupporting
confidence: 92%
“…Increases in SBP, cSBP, central and peripheral MAP, and cPP were observed in the hypertensive elderly females of our study compared to males, and these findings are in accordance with those of previous reports [29][30][31]. We used an oscillometric technique to measure brachial blood pressure, and a noninvasive tonometric system was used to analyze the pulse wave of the radial artery.…”
Section: Discussionsupporting
confidence: 92%
“…15 On the other hand, it is known that the prevalence of hypertension and cardiovascular diseases is significantly lower in premenopausal women compared to the male population of the same age, but this advantage is lost after the age of 45 when morbidity rates from cardiovascular diseases increase faster in the female population. 14,16,17 The next comorbidity in terms of frequency in our patients is thyroid disease, with 31 subjects suffering from it, and the same number suffering from diabetes. Thyroid diseases occur more often in the female population, their incidence is 5-20 times more common in women than in men.Research showed that the incidence of increased TSH in the general female population is 7.6%, while it is 17% in women over 70 years old.…”
Section: Discussionmentioning
confidence: 91%